Soci-Demographic Factors Influencing Intestional Parasitic Infection among Children in Bauchi Local Government Area, Bauchi State - Ahmadu, Adamu; A. B., Samaila; Gital, Kasimu, Gidado; Mohammed, Abdullahi, Saleh; J. I., Kyamru (RA Journal of Applied Research, 2022)
The study was conducted to investigate the socio-demographic factors influencing intestinal parasite infection among children in Bauchi metropolis, Bauchi state. The objectives of the study were to determine the prevalence of human intestinal parasite infection in the area of study, determine the influence of demographic of age of the infected children. Stool samples were collected from five hundred and sixty-two children. The samples were treated and examined microscopically for ova, cyst and eggs of intestinal parasite. The socio-demographic factorss were determined using questionnaire and anthropometric measurement. The result reveals that many children (28.11%) are infected with intestinal parasite. Ascaris lumbricoida, Trichuris trichura, Hookworms and eterobias vermicularis are the common prevailing parasites. While Giadia lamblia is the least common occuring parasite It was also discovered that there is no discrimination of infection among sexes. However, the infection is found to be more common among certain age group (0-4 years). It was concluded that the prevalence of intestinal parasite infection among children is increasing compared to previous studies and the increase is related to poor socio-demographic factors of the children. It is therefore, recommended that there is need to embark on health education on prevention and control measures of intestinal parasite and government should strengthen and support WHO program of providing free antihelminthes drugs to children.